Structure of blue copper proteins: electron-transfer kinetics - Galijašević, Semira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
In electron-transfer, the change in the oxidation state of the reactants is generally accompanied by structural changes, which influence the electron-transfer kinetics. Previous studies on the systems of Cu(II/I) complexes involving cyclic tetrathiaether ligands indicated that inversion of coordinated donor atoms may be a primary factor in controlling gated electron transfer. Complex formation and isopmerization studies on [14]aneN4 type complexes have demonstrated that coordinated N atoms are shown to invert since they must undergo a hydrogen abstraction prior to inversion. In the systems with [14]aneNxS4-x ligands, there is a choice of N or S inversion. This study has been conducted to determine the effect of inversion of coordinated N atoms on electron-transfer rates as a function of different concentrations of water as hydrogen ion acceptor existing in aprotic solvent (acetonitrile). Data on electron-transfer kinetics are presented here. Possible conformational changes and kinetics pathways for N-S mixed donor complexes are discussed.